1993
DOI: 10.1111/j.0022-3646.1993.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

REVEALING GENETIC MARKERS IN GELIDIUM VAGUM (RHODOPHYTA) THROUGH THE RANDOM AMPLIFIED POLYMORPHIC DNA (RAPD) TECHNIQUE1

Abstract: The recently developed random amplified polymorphic DNA technique was evaluated as a method for characterizing isolates of the agarophyte Gelidium vagum Okamura. Reaction conditions for single primer polymerase chain reaction were optimized to obtain a high degree of reproducibility of the amplified bands generated from purified G. vagum DNA. A total of 165 primers, including both (A + T)‐ and (G + C)‐rich sequences, was screened for DNA amplification using template DNA from a single Gelidium isolate. None of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 24 publications
1
30
1
Order By: Relevance
“…Similarly, genetic diversities of cox1 (Hd, 0.809 ± 0.026; π, 0.109 ± 0.009) for G. vagum were relatively high. Our results are consistent with previous reports (Patwary et al 1993) that G. vagum isolates have sufficient genetic diversity for conducting a heterosis experiment using random amplified polymorphic DNA methods. In contrast, genetic diversities were relatively low (Hd, 0.711) in G. elegans (Kim et al 2012) and (Hd,0.757) in Gracilaria vermiculophylla (Ohmi) Papenfuss (Kim et al 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, genetic diversities of cox1 (Hd, 0.809 ± 0.026; π, 0.109 ± 0.009) for G. vagum were relatively high. Our results are consistent with previous reports (Patwary et al 1993) that G. vagum isolates have sufficient genetic diversity for conducting a heterosis experiment using random amplified polymorphic DNA methods. In contrast, genetic diversities were relatively low (Hd, 0.711) in G. elegans (Kim et al 2012) and (Hd,0.757) in Gracilaria vermiculophylla (Ohmi) Papenfuss (Kim et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Gelidium vagum serves as an excellent model system for the study of heterosis in red algae because fronds can readily be grown under laboratory conditions and the sexual reproductive cycle can be completed in a few weeks under optimum conditions (van der Meer and Patwary 1991, Patwary et al 1993, Patwary and van der Meer …”
Section: Introductionmentioning
confidence: 99%
“…Gelidium (Rhodophyta): Patwary et al, 1993). The levels of polymorphism generated by the four random primers in the present study were much higher than those detected in broccoli and cauliflower cultivars (Hu & Quiros, 1991) and celery cultivars (Yang & Quiros,i993).…”
Section: Discussioncontrasting
confidence: 59%
“…The reasons for this are not clear but the absence of the band may be due to an amplification error related to competition among loci for a limiting amount of enzyme (Patwary et al, 1993). This needs to be examined further, by testing more samples within the genus Turbinaria as well as other genera within the family Sargassaceae and other members of the Phaeophyta.…”
Section: Discussionmentioning
confidence: 99%
“…In our preliminary tests using PCR amplifications with frozen fish tissue samples, we found that fewer than 40 cycles produced faint fragment patterns with many primers and we routinely used 40 cycles as a standard technique. In addition the PCR has been shown to be very sensitive to changes in concentration of magnesium ions, primer, and template, and to annealing temperature, all of which can affect the number and intensity of bands (Devos & Gale 1992;Ellsworth et al 1993;Patwary et al 1993;Penner et al 1993). Furthermore some primers have been shown to give more reproducible results than others (Penner et al 1993).…”
Section: Discussionmentioning
confidence: 99%